The Evolution of Imam Hatip Schools in Turkiye: From Kemalist Secularism to the Educational Politics of the AKP Era - Yılmaz, Mustafa Necati; Çelik, İbrahim Şevket (Bestari, 2025)
This article analyzes the historical and political evolution of Imam Hatip schools in Turkiye, tracing their transformation from marginal religious institutions under Kemalist secularism to significant contributors to national education during the AKP administration. Drawing on archival research, policy documents, and interviews with educators, the study examines how shifts in political ideology have shaped curriculum design, school governance, and public perceptions. The findings reveal that Imam Hatip schools have expanded both numerically and functionally, embodying a hybrid identity between general and religious education. However, the expansion also raises debates regarding educational equity, ideological influence, and academic outcomes. The article argues that the Imam Hatip model reflects broader tensions between secular republican values and religiously oriented educational policies. This study provides insight into the complex interplay between religion, politics, and schooling in contemporary Turkiye.